2022
DOI: 10.1097/corr.0000000000002314
|View full text |Cite
|
Sign up to set email alerts
|

What Proportion of Patients With Musculoskeletal Tumors Demonstrate Thromboelastographic Markers of Hypercoagulability? A Pilot Study

Abstract: Background Thromboelastography (TEG) is a point-ofcare venipuncture test that measures the elasticity and strength of a clot formed from a patient's blood, providing a more comprehensive analysis of a patient's coagulation status than conventional measures of coagulation. TEG includes four primary markers: R-time, which measures the time to clot initiation and is a proxy for platelet function; K-value, which measures the time for said clot to reach an amplitude of 20 mm and is a proxy for fibrin cross-linking;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Our finding that increased age was associated with a greater incidence of thromboembolic events corroborates the findings of prior studies, which have revealed hypercoagulability in older musculoskeletal oncology patients 3 . From a mechanistic standpoint, this hypercoagulability is thought to result from accumulation of plasma coagulation factors and changes to the endothelium that result in progressive dysfunction over time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that increased age was associated with a greater incidence of thromboembolic events corroborates the findings of prior studies, which have revealed hypercoagulability in older musculoskeletal oncology patients 3 . From a mechanistic standpoint, this hypercoagulability is thought to result from accumulation of plasma coagulation factors and changes to the endothelium that result in progressive dysfunction over time.…”
Section: Discussionsupporting
confidence: 92%
“…From a mechanistic standpoint, this hypercoagulability is thought to result from accumulation of plasma coagulation factors and changes to the endothelium that result in progressive dysfunction over time. In a previous study of musculoskeletal oncology patients presenting for surgery, patients with markers of hypercoagulability on thromboelastography had a mean age of 59 years compared with 44 years among those with normal results 3 . The results of the present study also suggest an increased index of suspicion for perioperative VTE among patients undergoing tumor resection and endoprosthetic reconstruction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A multicenter collaborative study (ideally prospective and randomized) might offer information about the most effective regimen for patients with primary sarcoma or bone metastasis who undergo major surgery, the optimal duration of thromboprophylaxis to be used, and whether individualized VTE prophylaxis is required. Distinguishing hypercoagulability driven by platelet hyperfunction and hypercoagulability driven by enzymatic hyperactivity that catalyzes fibrin crosslinking may inform the selection of chemoprophylaxis drugs (antiplatelet or anticoagulant) based on information derived from TEG [7].…”
Section: How Do We Get There?mentioning
confidence: 99%
“…Thromboelastography was used to assess thromboembolic risk in patients with malignant bone and soft tissue tumors [7]. The authors found advanced age, female sex, and soft tissue—not bone tumors—were associated with hypercoagulability using this technique.…”
mentioning
confidence: 99%